Profile of Shiga toxin-producing Escherichia coli strains isolated from dogs and cats and genetic relationships with isolates from cattle, meat and humans. - Bentancor, A. (2012)
Pets can be reservoirs of Shiga toxin-producing Escherichia coli (STEC) strains. The aim of this study was to examine nine strains belonging to several serotypes (O91:H21, O91:H16, O178:H19, O8:H19, O22:H8, O22:HNT, ONT:H8), previously recovered from cats or dogs. To this end, we assessed a set of additional virulence genes (stx(2) subtype, subAB, ehxA, eae and saa), cytotoxic activity, and genetic relationships with strains isolated from cattle, meat and humans using pulsed-field gel electrophoresis (PFGE). Most of the isolates carried the stx(2) and/or stx(2vh-b) sequences, while only the O91:H21 isolate presented the mucus-activatable stx(2d) variant, as confirmed by sequencing the genes of subunits A and B. All the strains showed cytotoxic activity in cultured cells. One of the two O178:H19, selected for its high level of cytotoxicity in Vero cells, showed the ability to cause functional alterations in the human colon mucosa in vitro. None of the strains possessed the subAB, eae or saa genes and only the strains belonging to serotype O8:H19 carried the ehxA gene. The isolates shared 90-100% similarity by PFGE to epidemiologically unrelated strains of the corresponding serotypes recovered from cattle, meat or humans. Our results demonstrate that dogs and cats may have a role in the infection of humans by STEC, probably serving as a vehicle for bovine strains in the cycle of human infection, and thus emphasize the health risks for owners and their families.